Atmospheric Science at NASA A History - Conway, Erik M. (Johns Hopkins University Press, 2008)
Honorable Mention, 2008 ASLI Choice Awards. Atmospheric Science Librarians InternationalThis book offers an informed and revealing account of NASA's involvement in the scientific understanding of the Earth's atmosphere. Since the nineteenth century, scientists have attempted to understand the complex processes of the Earth's atmosphere and the weather created within it. This effort has evolved with the development of new technologies-from the first instrument-equipped weather balloons to multibillion-dollar meteorological satellite and planetary science programs. Erik M. Conway chronicles the history of atmospheric science at NASA, tracing the story from its beginnings in 1958, the International Geophysical Year, through to the present, focusing on NASA's programs and research in meteorology, stratospheric ozone depletion, and planetary climates and global warming. But the story is not only a scientific one. NASA's researchers operated within an often politically contentious environment. Although environmental issues garnered strong public and political support in the 1970s, the following decades saw increased opposition to environmentalism as a threat to free market capitalism. Atmospheric Science at NASA critically examines this politically controversial science, dissecting the often convoluted roles, motives, and relationships of the various institutional actors involved-among them NASA, congressional appropriation committees, government weather and climate bureaus, and the military.